2020
DOI: 10.1200/po.19.00227
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Opportunities and Challenges for Patients With Sarcoma as a Result of Comprehensive Genomic Profiling of Sarcoma Specimens

Abstract: PURPOSE Comprehensive genomic profiling (CGP) of sarcomas is rapidly being integrated into routine clinical care to help refine diagnosis and prognosis and determine treatment. However, little is known about barriers to successful CGP or its clinical utility in sarcoma. We set out to determine whether CGP alters physician treatment decision-making, and whether sarcoma subtypes influence the frequency of successful technical performance of CGP. METHODS A single-institution study evaluated profiling outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This is the first report to show that the proportion of patients receiving genomically matched therapy was significantly higher among those with common cancers (16.2%) than non‐common cancers (9.4%) ( p = 0.0365), which confirmed our hypothesis that the clinical utility of CGP tests might differ between patients with common and non‐common cancers. Current CGP tests are primarily based on DNA sequencing that cannot detect all gene fusions, which could have significant clinical implications for diagnosis and treatment‐related decisions in patients with non‐common cancers, such as sarcoma and pediatric cancer 16,17 . Additionally, patients with non‐common cancers have less opportunity to participate in IND trials than those with common cancers (Figure S2A–C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first report to show that the proportion of patients receiving genomically matched therapy was significantly higher among those with common cancers (16.2%) than non‐common cancers (9.4%) ( p = 0.0365), which confirmed our hypothesis that the clinical utility of CGP tests might differ between patients with common and non‐common cancers. Current CGP tests are primarily based on DNA sequencing that cannot detect all gene fusions, which could have significant clinical implications for diagnosis and treatment‐related decisions in patients with non‐common cancers, such as sarcoma and pediatric cancer 16,17 . Additionally, patients with non‐common cancers have less opportunity to participate in IND trials than those with common cancers (Figure S2A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Performing CGP tests earlier in the course of the disease could minimize the attrition of patients qualifying for IND trials. To a High tumor mutation burden corresponding to ≥10 mutations per megabase.treatment-related decisions in patients with non-common cancers, such as sarcoma and pediatric cancer 16,17. Additionally, patients with non-common cancers have less opportunity to participate in IND trials than those with common cancers (FigureS2A-C).…”
mentioning
confidence: 99%
“…In addition, comprehensive genomic profiling (CGP) is the sequencing of DNA and RNA from tumor samples, which enables the identification of known and novel alterations that may drive oncogenicity. Therefore, it is not surprising that CGP is increasingly being used in the evaluation and management of sarcomas ( 12 ). For instance, Wu et al ( 13 ) reported a case of disseminated primary pulmonary artery sarcoma achieving clinical tumor response to olaparib based on genetic alterations detected by CGP, which involved the DNA repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, the results of the Sarcoma Decision Impact Clinical Trial study have been published by the Foundation Medicine group [ 164 ]. This study applied the strategy of comprehensive genomic profiling to sequence both DNA and RNA from sarcoma tumor samples, with the aim to identify known and novel alterations that may drive oncogenicity and potentially impact on physicians’ treatment decision-making.…”
Section: Future Directionsmentioning
confidence: 99%